Monitoring of forskolin production from roots and callus by HPTLC in Coleus forskohlii Briq. - PAP, S MALATHY, J S (Journal of Spices and Aromatic Crops, 1999)
High Performance Thin Layer Chromatography was a sensitive and accurate method for detection and estimation of forskolin in roots and by tissue culture of Coleus forskohlii. Maximum absorption was observed at 315 nm using fluorodensitometric analyis. Forskolin production was observed in callus cultures from leaf, stem and root origin as well as roots of in vitro grown plants.